Composition, Distribution, Fishing Activities, and Physico-Chemical Characteristics: The Case of Jemma and Wonchit Rivers, Amhara Region, Ethiopia - Dereje Tewabe; Birhan Mohamed; Mihret Endalew; Binyam Hailu (Global Journal of Allergy - Peertechz Publications, 2016)
The distribution of fish species in Jemma and Wonchit Rivers was studied from November 2012 to May 2014 based on samples collected during wet and dry seasons using gillnets of 60, 80, 100, 120 and 140 mm stretched mesh sizes. Labeobarbus intermedius, Labeobarbus nedgia, Heterobranchus longifilis, Bagrus docmak, Varicorhinus beso and Oreochromis niloticus are commercially important fish species found in both rivers of the pooled experimental fish catch. But, Synodontis schall, Ramias loti, Labeo forskhalii, Tilapia rendelii, Mormyrus kannume and Bagrus bajad are found in river Jemma only. The high level of pH in Wonchit (9.14) may be lethal for some of the fishes that found in the river. The pH in Jema (8.79) might indicate higher productivity of water, but it is very approximate to the higher limit. The most likely explanations for the fishing activity of fish species are the increase of the illegal commercial plant poisoning material used for fishing activities that seriously affects the riverine fishery of the surroundings. Fishery targeting their aggregations in the pooled, and the increasing trend of the degradation of spawning and nursery habitats by poisoning plant in the water pooled area should be protected. This means, there should be a need for urgent development of a management plan focusing on ensuring sustainable utilization of a resource. Control the production grounds of Millettia ferruginea poisoning plant from its source and its market is important.